ANALISIS PELAKSANAAN PEMBELAJARAN JARAK JAUH MELALUI FOCUS GROUP DISCUSSION - Lies Nurhaini (Bajang Institute, 2022)
This study use the Participatory Action Research (PAR) method and using the Forum Group Discussion (FGD) technique. The objectives of this FGD activity are (1) to identify the type of platform used in distance learning, (2) to find out the obstacles in implementing distance learning, and (3) to find out how strategies can be used to overcome the existing obstacles. The results of the FGD at SMK Negeri Jumantono are: (1) Teachers have tried to vary the platform as a means of distance learning such as whatsapp groups, google classroom, google forms, google sites, zoom cloud meetings, youtube, and various other social media; (2) The implementation of PJJ experienced several obstacles, such as signals, student activity, interest and motivation to learn; (3) formulating several strategies to improve the quality of distance learning, both from the pedagogic competence of teachers and their supporting facilities.